Kolaborasi Stakeholder terhadap Program Rehabilitasi Sosial Rumah Tidak Layak Huni Kota Cilegon - Amalia, Risty; Rahmawati (Epistemik Press, 2024)
The Social Rehabilitation Program for Uninhabitable Houses (RS-RTLH) from the Cilegon City Government is still needed considering that there are still many houses that are uninhabitable. Collaboration in implementing RS-RTLH in Cilegon City involves various parties, such as the Social Service, CCSR (Corporate Social Responsibility Cilegon), and Baznas, who work together in building RS-RTLH in accordance with the joint agreement stated in several letter numbers, namely the Social Service Number 460/14/pemt/2020, CCSR Number 045/CCSR-Dinsos/X/2020, and Baznas Number 497/pengurus/BAZNAS CLG/X/2020. This research aims to explore collaboration between stakeholders in RS-RTLH in Cilegon City using the theoretical model of Ansell and Gash (2008). The research method used is qualitative with a descriptive design. The research results show that collaboration between stakeholders in the implementation of RS-RTLH still follows the rules of each stakeholder. However, there are still shortcomings, such as the lack of meeting forums provided by the Regional Government to facilitate communication and program reporting. Therefore, researchers recommend that the Cilegon City Government make special regulations between stakeholders in the form of Regional Regulations or Mayor Regulations, as well as directing the community to support the Social Rehabilitation Program for Uninhabitable Houses (RS-RTLH).